Influence of slow sand filter cleaning process type on filter media biomass: backwashing versus scraping. (1st February 2021) - de Souza, F.H.; Roecker, P.B.; Silveira, D.D.; Sens, M.L.; Campos, L.C.
Highlights: For the first time, a biomass approach was used to investigate backwashed SSF. Biomass accumulated differently in scraped and backwashed slow sand filters. 16S rRNA sequencing indicated variation of the bacterial community between filters. Biomass was better preserved in different trophic levels after backwash. The filtrate was of good quality in BFS and ScSF despite their biomass differences. Abstract: Biomass was assessed as a new approach for evaluating backwashed slow sand filters (BSF). Slow sand filtration (SSF) is a simple technology for water treatment, where biological mechanisms play a key role in filtration efficiency. Backwashed slow sand filters were previously recommended for small-scale filters ( 1 m² of filtration area) as an alternative to conventional filters that are usually cleaned by scraping (ScSF). Biomass was never evaluated in BSF, which is a gap in the knowledge of this technology, considering the importance of its biological mechanisms. Therefore, for the first time, two filters operating under the same conditions were used to compare the influence of backwashing on biomass; one filter was cleaned by backwashing and the other by scraping. Biomass along the filter media depth (40 cm) was assessed by different techniques and compared in terms of cellular biomass (by chloroform fumigation), volatile solids, bacterial community (by 16S rRNA gene sequencing), and observations by scanning electron and fluorescence microscopy. Filters were also monitored and compared regarding filtered water quality and headloss; their differences were related to the different cleaning processes. Overall, filtered water quality was acceptable for slow sand filter standards (turbidity < 1 NTU and total coliform removal > 1 log). However, headloss developed faster on scraped filters, and biomass was different between the two filters. Backwashing did not significantly disturb biomass while scraping changed its surface sand layers. Cell biomass was more abundant and spread across the filtration depth, related to lower headloss, turbidity, and cyanobacterial breakthrough. These results agreed with the water quality and microscopy observations. The bacterial community was also less stratified in the backwashed filter media. These results expand the knowledge of backwashing use in slow sand filters, demonstrating that this process preserves more biomass than scraping. In addition, biomass preservation can lead to bacterial selectivity and faster filter ripening. Considering the importance of biomass preservation on slow sand filtration and its biological filtration mechanisms, the results presented in this paper are promising. The novel insight that BSF can preserve biomass after backwashing may contribute to increasing its application in small communities. Graphical abstract: Image, graphical abstract